Marcos ; Stay or not stay The other side [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
A debate between loyalists, oppositionists to have the remains of the former President Ferdinand E. Marcos burried in the Philippines ; also discusses the issue of the American bases in the Philippines ; an interview with Corazon Aquino.